1996
DOI: 10.1002/(sici)1097-0142(19960301)77:5<850::aid-cncr7>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Early gastric lymphoma: A clinicopathologic study of ten patients, literature review, and comparison with early gastric adenocarcinoma

Abstract: Surgical treatment with a wide resection of the stomach and extensive lymph node dissection is necessary for early gastric lymphomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
2
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
0
20
2
1
Order By: Relevance
“…As for the treatment of the superficial spreading type of early gastric cancer, we must first distinguish it from other diseases, namely the polypoid type of malignant lymphoma, multiple polyposis, and chronic gastritis [28][29][30][31]. After a diagnosis of the superficial spreading type of early gastric cancer is made, surgeons should understand the nature of the disease before operating.…”
Section: Discussionmentioning
confidence: 99%
“…As for the treatment of the superficial spreading type of early gastric cancer, we must first distinguish it from other diseases, namely the polypoid type of malignant lymphoma, multiple polyposis, and chronic gastritis [28][29][30][31]. After a diagnosis of the superficial spreading type of early gastric cancer is made, surgeons should understand the nature of the disease before operating.…”
Section: Discussionmentioning
confidence: 99%
“…However Turkish and Indian series suggested that intestinal lymphomas have been more predominant than gastric lymphoma in those regions [12,13] . Gastric lymphomas are prevalent in patients aged more than 50 years, however it still has been reported in the second decade of life [14,15] . Reported median age is 60-65 years and males are 2-3 times more affected than females [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Primary gastric lymphoma arises from the mucosal or submucosal layer and spreads diffusely into the mucosa and submucosa, and the tumor extends along the surface of the gastric wall, usually without lymph node involvement (6,17,35) . In this situation, gastroscopy may not be capable of detecting the lesion, due to the lack of suggestive alterations, such as polypoid or ulcerated lesions or also diffuse thickening of gastric folds (14,30) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, postoperative chemotherapy may be used to inhibit recurrence of neoplasm in the remaining stomach and eradicate microscopic residual disease (16,23,29) . Radiotherapy directed towards the framework supporting the stomach and the para-aortic lymph nodes has been demonstrated to be beneficial for patients with involvement of lymph nodes and disease that is locally advanced or cannot be extirpated (13,17) . Radiation was used post-operatively in high-and low-grade lymphomas, for any residual tumors in stages I and II in order to improve the disease free survival (17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation